SISTEM INFORMASI PENJUALAN BENIH IKAN DI ANTOK FARM BERBASIS WEB - , WAHYU HUDAYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The system used in the sale of fish seed in Antok Farm still a manual. Transaction data is only written in book. This makes the reporting process becomes longer and making decision becomes difficult. Marketing process is still using blogs or free advertising that has limited facilities. A proper solution to deal the problem is an fish seed sales information system that to deal sales data processing, fish seed data, city data, customer data, and transaction data. Also, this system has an graphics facility to used making decision in each period of decline or increase in the sale of fish seed and the process printing system reports. The information system is developed using Laravel software framework, PHP Programming language, and MySQL database. This information system is expected capable handle processing fish seed data, transaction data, ease the bookkeeping process and reporting process.